Signature of the maturity states of tropical climacteric fruits - De-Armas-Costa, Ricardo Joaquín; Martín-Gómez, Pedro Fernando; Rangel-Díaz, Jorge Eliecer (Universidad Pedagógica y Tecnológica de Colombia, 2020)
It is intended to publicize unpublished concepts to the community interested in the development of tropical climacteric fruits. Concepts developed in the doctoral thesis of Agrociencias called Numerical model to determine the ripening stages of gulupa fruit (Passiflora edulis Sims) by digital image, applying the Radon transform. These are the concepts: 'maturation matrices',' high resolution matrices', 'average maturation matrices',' deviation maturation matrices' and 'the signature (or signature in English) of the states of maturity'. This will allow: new representations of the variables of maturation, readings at the same time on all the variables of maturation and the visualization of patterns not explored until now. The maturation matrices are rectangular arrangements of the data taken by the ripening variables (physical, chemical, volatile components, nutritional contents and respiratory intensities) in the different stages of maturity established for climacteric fruits. The signatures are the graphs of the rows of the maturation matrices. To know the ripening variables of tropical climacteric fruits that are used in specialized scientific studies to determine ripening states, 40 articles were analyzed. In the analyzed sample, no high-resolution matrix was found, that is, no matrix involving all the maturation variables in its columns and handling at least four stages of maturity in its rows. The study that presented the best resolution was by Pilar et al. (2007) made with the tropical climacteric fruit Gulupa (Passiflora edulis Sims). This maturation matrix presented a resolution of 7 × 12, seven stages of maturity and twelve variables of maturation (eight physical and four chemical).